Directional multi–hop clustering routing protocol for wireless sensor networks. (18th September 2013) - Naeimi, Soroush; Chow, Chee–Onn; Ishii, Hiroshi
In recent years, cluster–based routing protocol in wireless sensor networks (WSNs) has drawn great attention among researchers. In this paper, we propose directional multi–hop clustering routing (DMCR) protocol for wireless sensor networks that chooses the least number of hops within a straight line through the most reliable path for data transmission. The route–finding process is carried out by using low–cost devices like angle of arrival (AoA) antennas. This mechanism is especially suitable for large network topologies because not only the energy efficiency of the network is improved by limiting the number of nodes participating in data transmission to the BS, but the necessity of re–clustering is also reduced by choosing the most energetic node nearest to the BS in each cluster to relay the aggregated data. The proposed protocol was proven through extensive simulations to outperform existing protocols in terms of network lifetime and data packet delivery.